x(x+6)+5(x+5)=42

Simple and best practice solution for x(x+6)+5(x+5)=42 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(x+6)+5(x+5)=42 equation:



x(x+6)+5(x+5)=42
We move all terms to the left:
x(x+6)+5(x+5)-(42)=0
We multiply parentheses
x^2+6x+5x+25-42=0
We add all the numbers together, and all the variables
x^2+11x-17=0
a = 1; b = 11; c = -17;
Δ = b2-4ac
Δ = 112-4·1·(-17)
Δ = 189
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{189}=\sqrt{9*21}=\sqrt{9}*\sqrt{21}=3\sqrt{21}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(11)-3\sqrt{21}}{2*1}=\frac{-11-3\sqrt{21}}{2} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(11)+3\sqrt{21}}{2*1}=\frac{-11+3\sqrt{21}}{2} $

See similar equations:

| 2(x+8)=16/3 | | -(x+-1)=-4x-2 | | 5r+2+47+86=180 | | 13x+19=3x+19 | | 3•(5m-4)•(m+2)=8 | | x+5(x+6)+5=42 | | 8w-()=-7w-3-() | | 3x-10=6x+14 | | -2(y-4y)+4=-6(2y-y)+3+11y | | 2000-25p=6000 | | x(x+6)+5=42 | | 3n-8=31-n | | m/27=14.58 | | x-3=x+6/2 | | 11n=23=6n-47 | | 5r–7=38 | | -4(1-6v)=92 | | (9,-2);m=3 | | 7.6+x=14.3 | | 2(x+8=16/3 | | x(x+6)=42 | | 6x5x=19 | | 8+4x+5=5x+3-x | | 18n+384=48-3n | | 22=2y-10 | | -2(x+6)+4=8(x+5)+1 | | 4x+1=10x-4 | | x+2=3x-8/2 | | x(x+6)=x+5 | | F(x)=2x^2-9x+6 | | xx+6=x+5 | | 16t2-40t+25=0 |

Equations solver categories